Theory of temperature-dependent electronic structure and photoemission of ultrathin ferromagnetic films - Reiser, D.; Henk, J.; Gollisch, H.; Feder, R. (Solid state communications, 1995)
Surfaces and ultrathin films of ferromagnetic transition metals are modelled by large clusters with periodic boundary conditions parallel to the surface. For given average magnetizations, which correspond to finite temperatures, frozen configurations of fluctuating local magnetic moments are determined subject to an assumed short-range magnetic order. Within a tight-binding formalism without spin-orbit coupling, we recursively calculate for these configurations the one-electron Green function matrix elements, which yield the spin- and layer-resolved density of states and the spin- and angle-resolved photoemission current. Numerical results are presented for two ferromagnetic monolayers of Co on Cu(0 0 1). Spin-resolved photoemission spectra obtained for an average magnetization 0.2 M ( T = 0) and moderate short-range order agree reasonably with experimental data measured at room temperature.